Cross‐Linking between Sodalite Nanoparticles and Graphene Oxide in Composite Membranes to Trigger High Gas Permeance, Selectivity, and Stability in Hydrogen Separation. (19th February 2020) - Guo, Hailing; Kong, Guodong; Yang, Ge; Pang, Jia; Kang, Zixi; Feng, Shou; Zhao, Lei; Fan, Lili; Zhu, Liangkui; Vicente, Aurélie; Peng, Peng; Yan, Zifeng; et al.
Abstract: Thin membranes (900 nm) were prepared by direct transformation of infiltrated amorphous precursor nanoparticles, impregnated in a graphene oxide (GO) matrix, into hydroxy sodalite (SOD) nanocrystals. The amorphous precursor particles rich in silanols (Si−OH) enhanced the interactions with the GO, thus leading to the formation of highly adhesive and stable SOD/GO membranes via strong bonding. The cross‐linking of SOD nanoparticles with the GO in the membranes promoted both the high gas permeance and enhanced selectivity towards H2 from a mixture containing CO2 and H2 O. The SOD/GO membranes are moisture resistance and exhibit steady separation performance (H2 permeance of about 4900 GPU and H2 /CO2 selectivity of 56, with no degradation in performance during the test of 50 h) at high temperature (200 °C) under water vapor (4 mol %). Abstract : Um H2 aaresbreite : Eine Vernetzung zwischen Sodalith (SOD)‐Nanopartikeln, die eine Lochweite von 2.9 Å aufweisen, mit flexiblen 2D‐Lagen von Graphenoxid (GO) in Membranen wurde erreicht. Dies führte zu einer hohen Gasdurchlässigkeit und erhöhten Selektivität für Wasserstoff aus einer Mischung mit CO2 und Wasser.